Impact of Sjögren’s disease and its immunological characteristics on reaching remission or low disease activity state in systemic lupus erythematosus patients: a propensity score-matched longitudinal study - Zhang, Haoze; Zhang, Huijuan; Gao, Dai; Ji, Lanlan; Hao, Yanjie; Zhang, Zhuoli (Frontiers in Immunology, 2025)
BackgroundSystemic lupus erythematosus (SLE) overlapping with Sjögren’s disease (SjD) or not may progress differently in the clinical course. We aimed to explore the impact of SjD on lupus low disease activity state (LLDAS) or remission achievement in a real-world cohort.MethodsThe medical records of patients in the Peking University First Hospital SLE (PKUFHS) cohort from 2007 to 2019 were retrospectively reviewed. Demographics, SLE and SjD features, treatment, and whether in LLDAS/remission on treatment (RONT) or not at each visit were collected. According to overlapped SjD and its immunological features, all patients were categorized into the following subgroups: SjD with anti-SSA single positivity, SjD with anti-SSA/SSB double positivity, SjD with baseline hypergammaglobulinemia, and those without SjD. The Cox proportional hazards model in propensity score-matched cohorts was used to estimate the impact of different SjD characteristics on LLDAS/RONT and each component after correcting for known confounders.ResultsA total of 9,415 visits originating from 626 SLE patients were included. Overlapping SjD was identified in 77 (12.3%) patients. Patients with SLE overlapping SjD were significantly older at onset and predominantly female with more frequent hematological involvement. Overlapping SjD and anti-SSA/SSB double-positive SjD were associated with 29%–38% and 50%–53% reduction, respectively, in RONT achievement in SLE patients. Both overlapping SjD and SjD with baseline hypergammaglobulinemia acted as protectors for LLDAS achievement with 24% and 31% increments, respectively, and anti-SSA single-positive SjD showed no definite effect. The most affected target component was normal serology, with hazard ratios of 0.64–0.85 for overlapping SjD and anti-SSA/SSB double-positive SjD, and 1.15–1.24 for SjD with baseline hypergammaglobulinemia.ConclusionsOverlapping SjD facilitated reaching LLDAS yet hampered further RONT, anti-SSA/SSB double-positive SjD acted as a hazardous factor, SjD with baseline hypergammaglobulinemia acted as a protective factor, and anti-SSA single-positive SjD acted as an irrelevant factor for RONT achievement.